British Thoracic Society national pleural procedures audit 2010. Issue 7 (7th April 2011) - Hooper, Clare; Maskell, Nick
Abstract : In this report, we detail the results of the 2010 BTS national pleural procedures audit, to which 58 hospitals covering a collective population of more than 20 million patients contributed data regarding local pleural procedure practice and training policies and the process and complications associated with a total of 824 chest drain insertions. The results highlight a promising increase in the use of real time ultrasound guidance for pleural procedures but also deficiencies in pre-procedure consent practice and a significant rate of avoidable minor complications such as drain fall-out and procedure related pain. Action points for improvement to local pleural procedure practice are suggested.